Factors that influence purchase of group health insurance by employer / Nurul Naima Mohammad Sukri - Mohammad Sukri, Nurul Naima (2010)
After many years of experiment and development of health care and coverage, the health care system is a critical for businesses to attract and retain qualified employees. Because beginning or emerging businesses may have more risk attached to them, it is imperative that they provide employment packages which satisfy employees. Employee benefits play an important part in employee compensation and benefit packages. Group health insurance is a policy that an employer purchases and offers it to eligible employees of that company as one of their benefits included in the job position. Many times the employee’s family members are offered the coverage as well. Most of employees today have group health insurance coverage with their employer or with the employer of a member in their family. Therefore, this research is conducted to determine factors that influence purchase of group health insurance by employers.